Pengaruh Job Demands terhadap Employee Well-Being pada Karyawan PT. X - Putri, Nia Gustina; Guspa, Anindra (ARZUSIN, 2024)
This study was conducted with a quantitative approach to eval_uate how job demands affect employee well-being in workers at PT. X. The sample consisted of all employees of PT. X, totaling 56 people. The measuring instrument used was the QEEW.2.0 scale modified by Rahayu (2019), and the employee well-being scale by Rahmi et al. (2021). As a result, the coefficient (ß = -0.380, p <0.05) gave a significant effect on employee well-being in workers at PT X.